2016
DOI: 10.1177/0267659116636211
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different types of inferior vena cava cannulae placement by transesophageal echocardiography and its impact on hepatic dysfunction

Abstract: TEE can be used to monitor IVC cannula position. A higher frequency of cannula malposition was observed with the straight cannula compared to the angled cannula, but was not found to be associated with hepatic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Although venous catheters may migrate into the hepatic vein with high frequency after surgical insertion from the right atrium [ 1 , 2 ], they rarely stray into the hepatic vein (HV) because of the anatomical structure and blood flow. Misplacement of venous cannula into the HV may lead to complications such as insufficient venous drainage and vascular injury [ 1 3 ]. We describe two cases of a guidewire and a venous canula, respectively, straying into the HV from the FV, possibly because of a Eustachian valve which is a structure at the junction of the right atrium and IVC.…”
Section: Introductionmentioning
confidence: 99%
“…Although venous catheters may migrate into the hepatic vein with high frequency after surgical insertion from the right atrium [ 1 , 2 ], they rarely stray into the hepatic vein (HV) because of the anatomical structure and blood flow. Misplacement of venous cannula into the HV may lead to complications such as insufficient venous drainage and vascular injury [ 1 3 ]. We describe two cases of a guidewire and a venous canula, respectively, straying into the HV from the FV, possibly because of a Eustachian valve which is a structure at the junction of the right atrium and IVC.…”
Section: Introductionmentioning
confidence: 99%
“…6 This study also showed that venous return was not impaired significantly, perhaps due to more proximal drainage ports on the utilized cannula, but that it is still possible to create passive hepatic congestion with harmful consequences. 7 Tempe et al studied whether the use of a straight or curved IVC cannula had any effect on hepatic dysfunction in 40 adults undergoing atrial septal defect repair with CPB. 7 Interestingly in this adult study, the authors showed a 50% cannula malposition incidence with the straight cannula compared with 20% with the curved cannula.…”
mentioning
confidence: 99%
“…7 Tempe et al studied whether the use of a straight or curved IVC cannula had any effect on hepatic dysfunction in 40 adults undergoing atrial septal defect repair with CPB. 7 Interestingly in this adult study, the authors showed a 50% cannula malposition incidence with the straight cannula compared with 20% with the curved cannula. Despite this finding, the pattern of postoperative liver enzyme change was not different between the 2 groups.…”
mentioning
confidence: 99%